Measurement of the 234U(n,f) cross section in the energy range between 14.8 and 17.8 MeV using Micromegas detectors - Kalamara, Antigoni; Chasapogloou, S.; Michalopoulou, V.; Stamatopoulos, A.; Eleme, Z.; Kokkoris, M.; Lagoyannis, A.; Patronis, N.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2020)
Neutron induced fission cross sections of actinides present special interest, since they lead to the design optimization of new generation reactors (Generation IV) as well as Accelerator Driven Systems (ADS). In the present work, the 234U(n,f) cross section was measured for which only a few available discrepant data exist in literature leading to poor evaluations. More specifically, four irradiations were performed at the 5.5 MV Tandem Accelerator Laboratory of NCSR “Demokritos” using quasi-monoenergetic neutrons produced by the 3H(d,n)4He reaction in the 14.8-19.2 MeV energy range. The 234U(n,f) cross section was measured relatively to the 235U(n,f) and 238U(n,f) reference ones and in order to perform the in-beam measurements for each of the actinide targets (234U, 238U, 235U), a Micromegas detector was used to record the fission fragments. The target-detector pairs were placed in an Al chamber filled with a Ar:CO2 (in 80:20 volume fraction) gas mixture at atmospheric pressure and temperature. The efficiency of the Micromegas detectors was estimated by Monte-Carlo simulations using the GEF and FLUKA codes. In addition, a detailed study of the neutron energy spectra was carried out by coupling both NeuSDesc and MCNP5 codes in order to take into account and correct for the contribution of low energy parasitic neutrons in the fission yields.